Calculation the thermodynamic properties of carbon monoxide gas using Monte Carlo simulation for adsorption researches - Nguyễn, Thành Được (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
The vapor-liquid equilibria of pure fluid carbon monoxide was predicted by Gibbs Ensemble Monte Carlo simulation method (GEMC) using our two new 5 - site intermolecular pair potentials ab initio. The ab initio pair potentials were established from coupled - cluster calculations, using the CCSD(T) level of theory and Dunning’s correlation consistent basis sets aug-cc-pVmZ (m = 2, 3) [1]. These potentials were also used for prediction of thermodynamics properties of vapor-liquid equilibria by GEMC. The coexistence phase diagram and thermodynamic properties based on them are found to be in very good agreement with experimental data.